Spring festivals - "Rosen, Mike" (Wayland, Hove, 1990)
"Seasonal Festivals" by Michael Rosen, published by Hodder Wayland in 1990. This English-language paperback is part of the "Seasonal Festivals" series and explores various well-known celebrations that occur throughout the year.